Tools for Activating Data Marketplace Toward Innovations with Data-mediated Communications - Hayashi, Teruaki; Ohsawa, Yukio (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book explores the employment of market mechanisms for data-interactive innovations. Based on the concept of innovators' marketplaces the book introduces a new concept of 'data jackets' to enable analysis of what kind of data exist, where they are located, and what kind of information they hold, even if the contents of data cannot be made publicly available. The book presents the concept of a marketplace for data in the case of data-interactive innovations. It introduces the marketplace as a platform for value-based exchange of data and - based on the idea of the innovators' marketplace - explains how data jackets can be utilized independently from the actual contents of the data. Specific chapters deepen the understanding of variables, constraints and intentions as constituent parts of data jackets, and the extension to variable quest, a process towards the design of data. A number of case studies showcases how the methods and processes presented can be employed in real-life contexts. Finally the authors present some extensions of the concept for web-based IMDJ and connections to business information system and an outlook.
Why A Market of Data? A Solution for Innovations -- Data-interactive Innovations as the Heart of Market of Data (MoDAT) -- Tools for Activating Data Marketplace (1) -- Tools for Activating Data Marketplace (2) -- Knowledge Structuring and Acquisition for Data Exchange -- Case Studies of Innovators' Marketplace on Data Jackets -- Conclusions.
Keywords: Business; Management science; Artificial intelligence; Business information services; Big data; Business and Management; Artificial Intelligence; IT in Business; Big Data